A escola de surdos e os alunos com altas habilidades/superdotação: uma problematização decorrente do processo de identificação das pessoas surdas - Negrini, Tatiane (2009)
This study is linked to Line Search Special Education Course of Master Program of Postgraduate Education at the Federal University of Santa Maria - UFSM that arose from the interest generated during the training in special education and participation in projects. Thus, the question that guided this research was how the process of identifying students with characteristics of High Abilities/Giftedness happens within the school / deaf community and the purposes for which the same? Accordingly, the overall objective was to discuss the effects that the process of identifying students with characteristics of High Abilities/Giftedness will produce within the school for deaf. The specific objectives were: a) organize and implement strategies for identifying students with High Abilities/Giftedness that take into account the experiences, language and expression of the deaf, b) discuss the process of identifying students with characteristics of High Abilities/Giftedness in the deaf community, examined the effects for the same c) to examine the perceptions of those involved in research on the students with High Abilities/Giftedness and the identification process. This research followed a qualitative approach, the type of case study therefore used as a base school, in the case, a school for deaf. The methodology was organized to achieve the process of identifying students with High Abilities/Giftedness school for deaf, involving the support of deaf people to adapt a list of items for observation in the classroom (GUENTHER, 2000), as well as the participation of teachers and students of the school, in other stages of the process. All steps were carried out on a journal in the field, leading to further appreciation of them. For data analysis, was performed a categorization, with appropriate highlighting of some aspects that are highlighted, among them, the deaf students identified with characteristics of High Abilities/Giftedness show features, attributes that can be evidenced in the school, taking into account the specificities of their language, culture, etc. and they can be observed at different times. It is important to emphasize that the identification process that allows these students to think about curriculum strategies to meet this demand, nurture opportunities for differentiated learning. Moreover, the educational context is surrounded by a larger network of relationships, which determine time and space in modernity.